Mental tests : their history, principles and applications - Freeman, Frank N. (Frank Nugent), 1880-1961 (Riverside textbooks in education., 1926)
In this book, the author has shown how the mental test idea was evolved out of the laboratory study of individual differences by psychologists, how the individual and then the group intelligence tests were developed, the application of statistical methods to the interpretation of the results, the creation of the different types of scales, the extension of the mental test idea in new directions, the technique and theory of the tests, the uses of the different types of mental tests, and their reliability, and has closed his treatment with two chapters on the interpretation of what the tests really measure and the nature of intelligence itself. The work of hundreds of individual investigators has been organized into a systematic treatise, and the place and work of each have been given their proper setting as parts of a great movement. The volume is accordingly offered to teachers of college and university classes in Mental Tests with confidence that it will prove as useful in this field as the texts now in use have done in the field of educational tests. (PsycINFO Database Record (c) 2005 APA, all rights reserved).